P289 The effectiveness of interventions to reduce psychological distress in patients with autoimmune rheumatic conditions: a systematic review of effectiveness. (23rd April 2022) - Hulley-Mills, Jamie; Sliverthorne, Christine; Jones, Bethan; Hooper, Jo; Robson, Joanne; Dures, Emma; Daniels, Jo; Thompson, Miles; Ndosi, Mwidimi
Abstract: Background/Aims: Autoimmune rheumatic conditions are multisystem chronic disorders associated with increased psychological distress. Consequences include poor medication adherence and high levels of disease activity. Psychological interventions may reduce distress and change health behaviours. We aimed to determine the effectiveness of interventions for psychological distress in patients with autoimmune rheumatic conditions. Methods: This was a systematic review of effectiveness which included randomised controlled trials of psychological interventions in adults with autoimmune rheumatic conditions. We searched MEDLINE, BNI, CINAHL, EMBASE, EMCARE, PsycINFO, NICE Evidence and The Cochrane Library. Two reviewers screened titles and abstracts and assessed the methodological quality of the included studies using Cochrane Risk of Bias 2 tool. Data were extracted by one reviewer and checked by a second. In each study, the effectiveness data were determined by extracting the reported means (and standard deviation) for each group and calculating the standardised mean differences using RevMan 5.4 software (The Cochrane Collaboration, 2020). The data on primary outcomes (anxiety and depression) are reported here. Results: The search identified 96 studies. The process of screening and assessing for eligibility resulted in 20 studies for inclusion. Of these, one study had an overall low risk of bias and 19 had 'some concerns', mainly due to inadequate blinding and no information on pre-specified analysis plan. Only eight studies reported the effects on anxiety and 10 studies reported on depression. These studies included 919 patients in total. Most interventions were based on cognitive behavioural therapy and the context of delivery ranged from face-to-face individualised treatment to online group therapy. They often included education on topics such as stress and fatigue. Interventions often trained participants to develop skills in relaxation, problem-solving, and thought reframing. Goal setting and action planning were common to help participants make behaviour changes and apply their learning. Table 1 summarises disease group, type of intervention, comparator, outcome measure, and effects. Conclusion: Conclusion: Most interventions were effective in reducing anxiety and depression in autoimmune rheumatic conditions. However, given the clinical heterogeneity and 'some concerns' about the included quality of studies, more work is needed to understand the mechanisms of the intervention effectiveness. Disclosure: J. Hulley-Mills: None. C. Sliverthorne: None. B. Jones: None. J. Hooper: None. J. Robson: None. E. Dures: None. J. Daniels: None. M. Thompson: None. M. Ndosi: None.